ANALISIS FRAMING KEPELATIHAN PATRICK KLUIVERT DI TIMNAS MELALUI MEDIA ONLINE DETIK.COM - Muhammad Irsyad Faizin; Andika Sanjaya (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
This study aims to analyze the framing of Patrick Kluivert's coaching news in the online media Detik.com after the change of Indonesian national team coach in early 2025. The method used is descriptive interpretative with a qualitative approach through observation and documentation techniques on 17 news items for the period January–October 2025. The analysis was conducted using the Pan and Kosicki framing model which includes syntactic, script, thematic, and rhetorical structures. The results show that Detik.com tends to frame Patrick Kluivert positively by emphasizing his professional, tactical, and hard-working image, although still presenting criticism of match results. Syntactically, the use of interesting titles and quotes maintains an objective impression. In the script and thematic structure, the media emphasizes strategy and professionalism, while rhetorically uses positive diction and appreciative sentences to strengthen the image. In addition, there is an application of agenda setting by highlighting certain aspects to shape public opinion. This study confirms that the media plays an important role in building perceptions through the choice of perspectives and language in sports reporting.